Case File: Use of POCUS for assessment of dyspnea in the Emergency Department - Jennifer Meloche (CINQUILL Medical Publishers Inc., 2016)
A 65 year-old man presented to the Emergency Department at Kingston General Hospital with progressive shortness of breath, fatigue, dull chest discomfort that worsened with deep breathing and exertion. The patient was referred to cardiology for congestive heart failure and ordered troponin, chest x-ray (CXR), and electrocardiogram (ECG).